OC-079 Previous exposure to hepatitis b infection and liver outcomes in a population with hepatitis c. (22nd June 2015) - Swann, R; Wang, H; Thomas, E; Innes, H; Schnier, C; Hutchinson, S; Mills, PR; Dillon, J
Abstract : Introduction: Coinfection with HCV and HBV is associated with adverse liver outcomes. 1 While most patients who are acutely infected with HBV in adulthood will clear the virus, up to 80% continue to have evidence of persistent HBV DNA in their liver. 2 The clinical impact of previous HBV infection on liver outcomes in HCV infection is unknown. In the UK, HBV vaccination is only targeted at high risk groups and uptake of this is incomplete. Therefore assessing any additional risk of liver disease posed by previous HBV infection is of importance to public health policy. We aimed to determine any association of previous HBV infection with adverse liver outcomes in a large Scottish cohort of HCV infected patients, using anti-HBV core antibody (Anti-HBc) positivity as a marker of previous exposure. Method: The Scottish HCV Clinical Database containing clinical data for all patients attending HCV clinics in participating health boards was linked to the HBV virology database and Information Services Division, Scotland data on mortality and hospital admission data. Duplicate patient records, those with no recorded positive HCV RNA and those with incomplete HBV status were excluded from the analysis. Univariate and multivariate cox regressional models and Accelerated Failure Time models were constructed for time to clinical diagnosis of cirrhosis and hepatocellular carcinoma. Models were fitted using both date of birth and date of diagnosis with last follow up or death used as censor date. Results: 9, 573 patient records were included in the analysis (197 HBsAg positive, 1723 Anti-HBc positive, HBsAg negative, 7653 Anti-HBc negative). Previous HBV infection (Anti-HBc positive, HBsAg negative) was significantly associated with development of cirrhosis (HR 1.46, 1.29–1.65) and development of HCC (HR 1.67, 1.17–2.37) on multivariate analysis. These associations remained significant in all models fitted. Other factors associated with poorer outcome were alcohol excess, older age, male sex and genotype 3 HCV. Achieving SVR and IVDU were associated with lower risk of cirrhosis and HCC. Conclusion: This is the largest study to date to show an association between previous HBV infection and adverse liver outcomes in HCV infection. Our data complements a growing body of evidence which suggests HBV infection may have adverse effects on liver health despite apparent clearance. This has important implications for the UK HBV vaccination policy and requires further investigation. Disclosure of interest: None Declared. References: Zarski JP, Bohn B, Bastie A, et al . J Hepatol. 1998;28:27–33 Sagnelli E, Imparato M, Coppola N, et al . J Med Virol. 2008;80:1547–1553